Peran Regulasi Otoritas Jasa Keuangan Dalam Mencegah Praktik Perbankan Abusive Lending Salsabila Nisa Aprilia, Baidhowi, Yustina Dhian Novita - Aprilia, Salsabila Nisa; B, Baidhowi; Novita, Yustina Dhian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Growth of the financial services sector The rapid growth of the financial services sector in Indonesia is also accompanied by the emergence of new challenges in banking practices, one of which is abusive lending. In banking practices, one of which is abusive lending. The practice this practice reflects a form of irregularities in the provision of credit that is carried outexploitative, non-transparent, and detrimental to customers. The Financial Services Authority (OJK). Financial Services Authority (OJK) as an independent institution tasked with regulating and supervising the financial services sector plays a strategic role in preventing and dealing with abusive lending the financial services sector plays a strategic role in preventing and addressing such practices this practice. This study aims to examine the role of regulations issued by OJK in preventing regulations issued by OJK in preventing abusive lending as well as evaluating the effectiveness of its implementation in practice. The method used is the normative juridical approach with descriptive-qualitative analysis techniques based on the review of laws and regulations, OJK policies, and relevant scientific literature relevant scientific literature. The results showed that OJK has issued a number of important regulations, such as POJK No. 1/POJK.07/2013, POJK No. 6/POJK.03/2015, and POJK No. 18/POJK.03/2015. POJK No. 18/POJK.03/2016, which regulates the principles of transparency, consumer protection, and risk management in lending protection, and risk management in lending. Nonetheless, implementation of these regulations still faces serious challenges, such as weak supervision of market behavior, low public financial literacy, and limited capacity for technology-based supervision.